Bayesian population pharmacokinetic modeling of florfenicol in pigs after intravenous and intramuscular administration. Issue 5 (5th July 2018) - Liu, Zhichang; Rong, Ting; Zeng, Dongping; Shen, Xiangguang; Ma, Xianyong; Zeng, Zhenling
Abstract: Bayesian population pharmacokinetic models of florfenicol in healthy pigs were developed based on retrospective data in pigs either via intravenous (i.v.) or intramuscular (i.m.) administration. Following i.v. administration, the disposition of florfenicol was best described by a two‐compartment open model with the typical values of half‐life at α phase ( t 1/2α ), half‐life at β phase ( t 1/2β ), total body clearance (Cl), and volume of distribution ( V d ) were 0.132 ± 0.0289, 2.78 ± 0.166 hr, 0.215 ± 0.0102, and 0.841 ± 0.0289 L kg −1, respectively. The disposition of florfenicol after i.m. administration was best described by a one‐compartment open model. The typical values of maximum concentration of drug in serum ( C max ), elimination half‐life ( t 1/2Kel ), Cl, and Volume ( V ) were 5.52 ± 0.605 μg/ml, 9.96 ± 1.12 hr, 0.228 ± 0.0154 L hr −1  kg −1, and 3.28 ± 0.402 L/kg, respectively. The between‐subject variabilities of all the parameters after i.m. administration were between 25.1%–92.1%. Florfenicol was well absorbed (94.1%) after i.m. administration. According to Monte Carlo simulation, 8.5 and 6 mg/kg were adequate to exert 90% bactericidal effect against Actinobacillus pleuropneumoniae after i.v. and i.m. administration.